The True Seed of Shalott (TSS) Technology Production on Trisula Variety in East Java - P.E.R. Prahardini; Tri Sudaryono (Indonesian Journal of Environment and Sustainable Development, 2018)
One of the onion increasing production problem is the lack of quality seeds availability. In order to provide high quality seeds of high yield and available throughout the year, an improvement of seed technology is required. One of the developing onion seed technologies is onion seeding through TSS (true seed of shallot). TSS technology development is expected to overcome the problem of onion seeding in Indonesia. East Java as one of the production centers of onion requires in developing onion seeding technology through TSS. This study aims to apply and develop TSS production technology using Trisula varieties which has been done from April to December 2016 in Tulungrejo village, Bumiaji district, Batu. The result of TSS production technology implementation indicates that Trisula variety is able to produce 110,5 kg TSS. Based on its agro-ecology, Batu area has the potential as the center of TSS production in East Java.Keywords: Onion, Technology, Trisula Varieties, True Seed of Shalot